2022
DOI: 10.1002/ldr.4444
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of soil microbe metabolic limitation was altered by the increased sheep grazing intensity in two contrasting grasslands: Implications for grassland management in semiarid regions

Abstract: Soil extracellular enzyme stoichiometry (EES) and microbial metabolic limitation deeply reflect soil quality. However, knowledge about the impacts of different grazing intensities on microbial metabolic limitation has not been well-documented.Herein, the influences of four sheep grazing intensities (ungrazed, UG; lightly grazed,LG; moderately grazed, MG; and heavily grazed, HG) on microbial metabolic limitation were investigated in typical steppe (14-year grazing) and desert steppe (17-year grazing). The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
3
1
Order By: Relevance
“…Results showed that soil available calcium (p = 0.0099), magnesium (p = 0.0099), and potassium (p = 0.0099) were identified as the most crucial factors that significantly explained the variation of soil microbial C limitation. This was also different from a recent finding from sheep grazing studies, which suggested that soil organic carbon and total nitrogen significantly affect soil microbial carbon limitation [11]. Furthermore, soil available calcium (p = 0.0099) and magnesium (p = 0.0198) were identified as the most crucial factors that significantly explained the variation of soil microbial nutrient (nitrogen and phosphorus) limitation (Fig.…”
Section: Grazing Changes Soil Microbial Element Limitationcontrasting
confidence: 90%
See 2 more Smart Citations
“…Results showed that soil available calcium (p = 0.0099), magnesium (p = 0.0099), and potassium (p = 0.0099) were identified as the most crucial factors that significantly explained the variation of soil microbial C limitation. This was also different from a recent finding from sheep grazing studies, which suggested that soil organic carbon and total nitrogen significantly affect soil microbial carbon limitation [11]. Furthermore, soil available calcium (p = 0.0099) and magnesium (p = 0.0198) were identified as the most crucial factors that significantly explained the variation of soil microbial nutrient (nitrogen and phosphorus) limitation (Fig.…”
Section: Grazing Changes Soil Microbial Element Limitationcontrasting
confidence: 90%
“…Ding et al [10] showed that grazing exacerbated the microbial carbon limitation of surface soil. Soil extracellular enzyme activity and microbial resource limitation profoundly reflect soil quality [11] and impact the carbon use efficiency of soil microbiota [12]. Therefore, understanding soil enzyme activity and soil microbial element resource limitations can enhance our understanding of soil carbon and nutrition supply from the perspective of microbial communities [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the very slow weathering rates of parent materials and the strong affinity of di‐ and trivalent cations as well as calcium towards phosphate (Elser, 2012; Westheimer, 1987), P mainly exists as persistent organic and inorganic forms in soils, leading to prevalent deficiencies in bioavailable P in most ecosystems (Lekberg et al., 2021; Liu et al., 2023). In contrast to agricultural systems with P fertilization, the P loss from soil–plant cycling in grasslands is primarily replenished through the acceleration of P recycling from plant litter driven by microorganisms (Helfenstein et al., 2018; Zhang, Song, et al., 2023). Thus, clarifying the responses of soil microorganisms in the P cycle is increasingly recognized as a major priority in grassland ecosystem management and restoration.…”
Section: Introductionmentioning
confidence: 99%